Digital Skill Confirmation Factor Analysis on the Use of Mobile Banking Services in the City of Surakarta - Meutria Salma; Refi Rifaldi Windya Giri (Ilomata International Journal of Management, 2023)
This study conducted in Surakarta, Indonesia aimed to examine the relationship between digital skills and mobile banking usage using Confirmatory Factor Analysis. The study revealed that operational mobile skills, information navigation skills, creative skills, and social skills were the factors that influenced mobile banking usage. However, despite the rapid development of mobile banking, there was still a digital divide. The study recommends modifying the index through Exploratory Factor Analysis for future research. The findings emphasize the significance of digital skills in mobile banking and can be useful for policymakers, mobile banking service providers, and users in Surakarta, Indonesia. This study contributes to the understanding of the relationship between digital skills and mobile banking usage and highlights the need for digital skill development in accessing mobile banking services in Surakarta, Indonesia.